Understanding Brazilians’ Intentions in Consuming Sustainable Fashion - Mikaela Daiane Prestes Floriano; Celso Augusto de Matos (BBR: Brazilian Business Review)
This study analyzed the determinants of sustainable fashion purchasing behavior, incorporating the following factors into the Theory of Planned Behavior: moral obligation, awareness of consequences, and previous sustainable purchasing behavior. A survey was carried out with Brazilian consumers of sustainable fashion, and a total of 179 responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that ‘moral obligation’ and ‘awareness of consequences’ had an impact on the behavioral attitude of sustainable fashion consumers. Furthermore, of the three TPB components, only attitude and ‘perceived behavioral control’ influenced the purchase intention. Finally, it was found that the actual consumption of sustainable fashion could be explained by the intention and the previous purchase behavior; also, age had a moderating influence on the relationship between the intention and the consumption of fashion. Therefore, this study provides marketers with comprehensive information about the psychological, social, cultural, and demographic determinants of sustainable fashion purchasing behavior.